Civilization aspects of economic integration processes - Kostenko, Natalia (Skhid, 2013)
The article clarifies nation’s interaction factors that represent the core of civilization development. Author considered views to economic integration through the prism of the past with extrapolation to the present. Arguments for regional economic integration were phrased as well.